2007
DOI: 10.1093/jhered/esm015
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Isolation and Linkage Group Identification in the Yellow Fever Mosquito Aedes aegypti

Abstract: Microsatellites have proved to be very useful as genetic markers, as they seem to be ubiquitous and randomly distributed throughout most eukaryote genomes. However, our laboratories and others have determined that this paradigm does not necessarily apply to the yellow fever mosquito Aedes aegypti. We report the isolation and identification of microsatellite sequences from multiple genomic libraries for A. aegypti. We identified 6 single-copy simple microsatellites from 3 plasmid libraries enriched for (GA)(n),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 85 publications
2
86
0
1
Order By: Relevance
“…However, it cannot be unequivocally discarded that the primers that were not amplified are not present in this species since some other variables in the flanking region could eventually affect the correct amplification . Nevertheless, it is necessary to point out that the frequencies and types of microsatellites may vary widely in many species of arthropods (Chambers et al, 2007); for example, these markers have been found to be limited and insufficient in Culicinae mosquitoes, as detected in A. aegypti (Huber et al, 1999;Fagerberg et al, 2001), Culex pipiens (Keyghobadi et al, 2004;Smith et al, 2005), and C. pipiens quinquefasciatus (Fonseca et al, 1998). Based on this reasoning, it is probable that the loci that were not amplified in this study are not definitively present in O. taeniorhynchus.…”
Section: Polymorphism Number Of Alleles Per Locus and Genetic Variabmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it cannot be unequivocally discarded that the primers that were not amplified are not present in this species since some other variables in the flanking region could eventually affect the correct amplification . Nevertheless, it is necessary to point out that the frequencies and types of microsatellites may vary widely in many species of arthropods (Chambers et al, 2007); for example, these markers have been found to be limited and insufficient in Culicinae mosquitoes, as detected in A. aegypti (Huber et al, 1999;Fagerberg et al, 2001), Culex pipiens (Keyghobadi et al, 2004;Smith et al, 2005), and C. pipiens quinquefasciatus (Fonseca et al, 1998). Based on this reasoning, it is probable that the loci that were not amplified in this study are not definitively present in O. taeniorhynchus.…”
Section: Polymorphism Number Of Alleles Per Locus and Genetic Variabmentioning
confidence: 99%
“…Microsatellites have been used as genetic markers in studies on a wide range of insect disease vectors (Chambers et al, 2007). Particularly in mosquitoes, they have been extensively applied to different species of the genus Anopheles, for conducting population genetic studies (Ayala et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Use of genetic markers for determining paternity in Ae. aegypti has been more challenging because of the low abundance of microsatellites 29 and the presence of multilocus microsatellite families linked with transposable elements, 30 although some microsatellite markers have been identified. 29,31 Genetic markers are currently being used in at least one study to examine polyandry in field-collected Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Para a espécie Ae. aegypti, diversos trabalhos já foram publicados isolando marcadores SSRs altamente polimórficos (Brown et al, 2011;Chambers et al, 2007;Huber et al, 2001;Slotman et al, 2006) o que facilita a utilização desses marcadores para estudo de populações desse mosquito vetor.…”
Section: Dna Nuclear -Microssatélitesunclassified